2018
DOI: 10.1016/j.jaap.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic conversion of beech wood pyrolytic vapors

Abstract: Catalytic fast pyrolysis (CFP) of beech wood chips was undertaken in a laboratory-scale fixed bed reactor equipped with a biomass semi-continuous dispenser. During pyrolysis, chars are retained on a quartz frit and the pyrolytic vapors are entrained through a fixed-bed catalyst to be converted. Several acidic catalysts such as zeolites H-Beta, zeolite HMFI and 5% Ni supported on HMFI were screened in this equipment. The Ni/HMFI catalyst was also tested in the presence of 1 vol.% of hydrogen in the feed stream.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
(62 reference statements)
0
8
0
1
Order By: Relevance
“…The use of all three ZSM-5 zeolite catalysts induced the production of ethane, ethylene, propane and propylene which were not produced by the non-catalytic pyrolysis. The production of these gases is indicative of enhanced cracking and dealkylation reactions catalyzed by ZSM-5 in accordance with its performance in biomass fast pyrolysis (Mullen and Boateng, 2010 ; Stephanidis et al, 2011 ; Wang et al, 2014 ; Margeriat et al, 2018 ). As discussed below, ethylene and propylene serve as precursors for the production of aromatics in the channels of ZSM-5.…”
Section: Resultsmentioning
confidence: 73%
“…The use of all three ZSM-5 zeolite catalysts induced the production of ethane, ethylene, propane and propylene which were not produced by the non-catalytic pyrolysis. The production of these gases is indicative of enhanced cracking and dealkylation reactions catalyzed by ZSM-5 in accordance with its performance in biomass fast pyrolysis (Mullen and Boateng, 2010 ; Stephanidis et al, 2011 ; Wang et al, 2014 ; Margeriat et al, 2018 ). As discussed below, ethylene and propylene serve as precursors for the production of aromatics in the channels of ZSM-5.…”
Section: Resultsmentioning
confidence: 73%
“…Energy & Fuels A labscale pyrolytic setup already described previously 10 was used. The wood chips were dried at 110 °C for 1.5 h before being placed in a gastight hopper and kept under N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies investigated the effect of different parameters of pyrolysis, such as the temperature, heating rate, particle size, reactor configuration, residence time, and presence and properties of catalysts; other works reported the impact of mixing the wood with different materials, such as plastics, agricultural residues, and municipal solid waste. The pyrolysis of demolition wood in a fluidized bed reactor has been mentioned as early as 2005, but the authors reported mostly experiments using pristine woods (pine, beech, and bamboo) and only experiment using demolition wood, which was simply compared in terms of liquid and char yields. Hwang et al carried out the pyrolysis of different municipal solid wastes, including wood chips (obtained from construction and demolition waste) and mixtures of paper/wood/plastics, at 500, 700, and 900 °C, the highest temperatures more closely related to gasification conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This trend was even more significant for Ni catalysts. The amount of alkylphenols was independent of the presence or absence of a catalyst …”
Section: Two-dimensional Gas Chromatography Characterization Of Pyrol...mentioning
confidence: 99%
“… a Links to references: , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , and . …”
Section: Principles Of Two-dimensional Gas Chromatographyunclassified